The Portrayal of Racial Discrimination Toward African-American People in Poor Little Black Fellow Short Story - Mardiana, Mardiana; Zamruddin, Mardliya Pratiwi; Max, Jonathan Irene Sartika Dewi (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
In a multicultural society, there is a possibility of the appearance minority group and the majority group. The minority group often gets discrimination treatment from the majority group. This research aims to find the portrayal of racial discrimination toward African-American people as a minority that appears in Poor Little Black Fellow short story. This research uses qualitative research design and multiculturalism as an approach. The researcher uses two main theories for this research, they are racial discrimination theory from Blank, et al., and characterization theory from Keenan. In this study, the researcher analyzed Arnold, The Pembertons, and Mappleton Villagers’ characters to see how racial discrimination is portrayed through their characterization. The results of this thesis show that there are several types of racial discrimination portrayed in the story through the characterization of those characters. Those types of discrimination are direct discrimination, subtle and unconscious discrimination, statistical discrimination and profiling, and organizational process. Those portrayals are presented mainly through indirect characterization and some direct characterization. Through the portrayal, it can be seen that racial discrimination can happen directly and indirectly. Keywords: multiculturalism, minority, racial discrimination, characterization, Poor Little Black Fellow